Analisis Sentimen Rakyat Brunei Terhadap Siaran Halaman ‘Brunei Fm’ Yang Bertajuk ‘Kes Pertama #Covid-19 Di Negara Brunei Darussalam' (International Journal of Linguistics and Indigenous Culture, 2024)
The COVID-19 pandemic has significantly impacted global societies, prompting widespread discussions on social media platforms. This study examines the sentiments expressed in Facebook comments by Bruneians regarding the first COVID-19 case in Negara Brunei Darussalam. Despite COVID-19 no longer being a global concern, understanding public sentiment during such crises remains critical for example, for future public health responses. Using a manual sentiment analysis approach, 50 comments from the post’s on ‘Brunei FM’ Facebook page were analyzed to categorize them into positive, negative, and neutral sentiments. The analysis revealed that 54% of the comments were negative, expressing fear, criticism, and blame, while 26% were positive, reflecting hope, support for health measures, and sympathy. The remaining 20% were neutral, focusing on information sharing and advice. This research aims to contribute to the field of manual sentiment analysis by providing a detailed examination of public reactions during a health crisis. The findings underscore the importance of effective communication strategies, community engagement, and responsive policy-making to address public concerns and enhance resilience during future health emergencies.